Teaching of the Speech Based on Reference Prediction Units to International Students - MUHAMMAD, LUDMILA PETROVNA; LEVINA, VERA NIKOLAYEVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article covers the simulation of a pedagogical strategy for forming skills to produce a monologic discourse based on reference prediction units. The purpose of the research was to identify optimal ways to form cognitive mechanisms for a monologic Russian-language discourse expansion with a rigid structure, primarily academic and academic-vocational, discourse in international students. Besides, it enables students to successfully predict and expand descriptive texts/discourses on various topics after one or two months. As a prospect for studying cataphoras in linguodidactics, let us note the following differentiation of student categories as an important point: extroverted students/introverted students.RESUMEN El artículo cubre la simulación de una estrategia pedagógica para formar habilidades con el fin de producir un discurso monológico basado en unidades de predicción de referencia. El propósito de la investigación fue identificar formas óptimas de establecer mecanismos cognitivos para una expansión monológica del discurso en ruso, con una estructura rígida, principalmente académico-vocacional, en el discurso de los estudiantes internacionales. Por otra parte, permite a los estudiantes predecir y expandir con éxito textos / discursos descriptivos sobre varios temas después de uno o dos meses. Como perspectiva para el estudio de las catáforas en lingüodidáctica, observemos la siguiente diferenciación de categorías de estudiantes como un punto importante: estudiantes extrovertidos / estudiantes introvertidos.